A First-in-Human Phase 1 Study of a Tumor-Directed RNA-Interference Drug against HIF2α in Patients with Advanced Clear Cell Renal Cell Carcinoma - Brugarolas, James; Obara, Gregory; Beckermann, Kathryn E.; Rini, Brian; Lam, Elaine T.; Hamilton, James; Schluep, Thomas; Yi, Min; Wong, So; Mao, Zhongping Lily; Gamelin, Erick; Tannir, Nizar M. (Clinical cancer research, 2024)
ARO-HIF2 is an siRNA drug designed to selectively target hypoxia-inducible factor-2α (HIF2α) interrupting downstream pro-oncogenic signaling in clear cell renal cell carcinoma (ccRCC). The aims of this Phase 1 study (AROHIF21001) were to evaluate safety, tolerability, pharmacokinetics, and establish a recommended Phase 2 dose. Subjects with ccRCC and progressive disease after at least 2 prior therapies that included VEGF and immune checkpoint inhibitors were progressively enrolled into dose-escalation cohorts of ARO-HIF2 administered intravenously at 225, 525, or 1,050 mg weekly. Twenty-six subjects received ARO-HIF2. The most common treatment emergent adverse events (AE) irrespective of causality were fatigue (50.0%), dizziness (26.9%), dyspnea (23.1%), and nausea (23.1%). Four subjects (15.4%) had treatment-related serious AEs. AEs of special interest included neuropathy, hypoxia, and dyspnea. ARO-HIF2 was almost completely cleared from plasma circulation within 48 hours with minimal renal clearance. Reductions in HIF2α were observed between pre- and post-dosing tumor biopsies, but the magnitude was quite variable. The objective response rate was 7.7% and the disease control rate was 38.5%. Responses were accompanied by ARO-HIF2 uptake in tumor cells, HIF2α downregulation, as well as rapid suppression of tumor produced erythropoietin (EPO) in a patient with paraneoplastic polycythemia. ARO-HIF2 downregulated HIF2α in advanced ccRCC-inhibiting tumor growth in a subset of subjects. Further development was hampered by off-target neurotoxicity and low response rate. This study provides proof of concept that siRNA can target tumors in a specific manner.